New fellow citizens in the Danish welfare state: Do non-western immigrants and their descendants support the core principles and values of the welfare state? - Breidahl, Karen Nielsen (Politica, 2017)
To what extent do non-Western immigrants and their descendants support the core principles of the Danish welfare state, and do they support these values to the same extent as ethnic Danes? These questions are examined based on survey data collected in 2014 among the Danish population and the five largest non-Western immigrant groups and their descendants. The article finds that there is overall and strong support for selected core values among the majority in all three groups as regards support for the duty to work, gender equality, state-financed welfare and that the state should increase its efforts for the needy. Within this overall pattern, the results also point out some interesting differences and similarities between non-western immigrants on the one hand and ethnic Danes on the other.